Faktor-Faktor Risiko Terhadap Keterlambatan Proyek Konstruksi di Wilayah Denpasar, Bali - I Gd Sastra Wibawa; I Made Anom Santiana; I Made Tapa Yasa; I Wayan Suasira (UM Purwokerto Press, 2021)
The construction projects are always faced with the possibility of risk problems. The rapid development in the Denpasar area is in line with the many construction projects, especially buildings such as hotel construction, construction of new school buildings, etc. For construction projects in Denpasar, risk control is necessary. In this regard, it is necessary to research the Analysis of Risk Factors. This study aimed to determine the dominant risk factors causing construction project delays, mitigation and risk ownership of the dominant risk factors. This research used the quantitative descriptive analysis method. The measuring instrument of this study used a questionnaire and interviews with contractor respondents. Based on the results, the dominant risk analysis was labor risk with an average frequency value of 13.70 and 17.13 consequences. The dominant question from the labor risk variable was the low productivity of the workforce due to lack of experience with a frequency percentage of 46.67% who answered rarely and 53.33% who often answered. In comparison, the percentage of consequences was 70.00% answered big and 30.00% answered very largely. Risk response that can be done is to recruit new workers and place them according to their skills. The study's ownership of risk was the contractor due to the contractor's error in employing workers in the field.